SISTEM PENUNJANG KEPUTUSAN UNTUK IDENTIFIKASI PENYAKIT MALARIA - Martin Johnsons; Dali Santun Naga; Dedi Trisnawarman (Jurnal Ilmu Komputer dan Sistem Informasi, 2019)
Malaria is one of serious threat that still lurking in Indonesia. In 2013, there are as many as fifteen provinces that exceeded national malaria’s prevalence number. The making of Decision support system for identifying malaria is targeted to lower malaria cases and reduce the risk of being late in handling malaria due to lacking of knowledge about malaria disease. This system is designed to count one’s odds (in percentage) of being infected by malaria. The DSS itself will be using Naïve Bayes method that is derived from probabilistic theorem of Bayes’.